Secretion of One Adipokine Nampt/Visfatin Suppresses the Inflammatory Stress-Induced NF-κB Activity and Affects Nampt-Dependent Cell Viability in Huh-7 Cells - Yi-Ching Lin; Hui-Chung Wu; Chen-Chung Liao; Yi-Chih Chou; Shwu-Fen Pan; Chi-Ming Chiu (Mediators of Inflammation, 2015)
Nampt/visfatin acts in both intracellular and extracellular compartments to regulate multiple biological roles, including NAD metabolism, cancer, inflammation, and senescence. However, its function in chronic inflammation and carcinogenesis in hepatocellular carcinoma (HCC) has not been well-defined. Here we use Huh-7 hepatoma cells as a model to determine how Nampt/visfatin affects cellular survival under oxidative stress. We found that the transition of Nampt/visfatin from intracellular into extracellular form was induced by H2O2 treatment in 293T cells and confirmed that this phenomenon was not due to cell death but through the secretion of Nampt/visfatin. In addition, Nampt/visfatin suppressed cell viability in oxidative treatment in Huh-7 cells and acted on the inhibition of hepatoma cell growth. Oxidative stress also reduced the Nampt-mediated activation of NF-κB gene expression. In this study, we identify a novel feature of Nampt/visfatin which functions as an adipokine that can be secreted upon cellular stress. Our results provide an example to understand how adipokine interacts with chemotherapeutic treatment by oxidative stress in HCC.